Percutaneous Fine Needle Biopsy in Pancreatic Tumors: A Study of 42 Cases - Piotr Lewitowicz; Jaroslaw Matykiewicz; Jacek Heciak; Dorota Koziel; Stanisław Gluszek (Gastroenterology Research and Practice)
The technological progress within the range of methods of pancreas imaging and their more common accessibility selects a group of patients requiring a microscopic diagnosis. Percutaneous fine needle aspiration biopsy under the control of ultrasonography (PCFNA/USG) is the method commonly used in determining the character of a focal pancreatic lesion. Aim of the Work. An assessment of the accessibility of PCFNA biopsy in the assessment of solid and cystic changes in a pancreas and the correlation of the results of imaging examination, cytological smear and concentration of a serous marker CA19-9. Material and Methodology. In our material we analysed 43 cases of tumors of the pancreas among the patients who were at the average age of 59 ± 10.4 (14 women, 28 men) diagnosed by PCFNA biopsy. Results. In a group we are 23 cases of cancer, 12 cases of inflammation and 7 cases of cellular atypia for which 2 cases of IPMN were included. The sensitivity of the method was 92.5% but specificity was 68%. In our opinion PCFNA/USG is a method of the comparable sensitivity and specificity with fine needle aspiration biopsy with EUS control and its efficiency depends to a considerable degree on experience and interdisciplinary collaboration.